Ruptured Common Femoral Artery Aneurysm or Abdominal Aortic Aneurysm? - Tetsuya Niino; Satoshi Unosawa; Haruka Kimura (Case Reports in Surgery)
We encountered a patient with a large retroperitoneal hematoma due to rupture of a common femoral artery aneurysm. A 77-year-old man was transferred to our hospital with left groin pain and shock. Computed tomography demonstrated a large retroperitoneal hematoma involving the left iliofemoral segment with extravasation of contrast into the left groin from a ruptured left common femoral artery aneurysm. The patient also had an abdominal aortic aneurysm. Reconstruction of the common femoral artery with a graft was performed successfully. The patient had an uneventful postoperative course and subsequently underwent Y-graft replacement of the abdominal aortic aneurysm.